Chemical fluctuation enabling strength-plasticity synergy in metastable single-phase high entropy alloy film with gigapascal yield strength. (April 2021) - Zhang, J.Y.; He, Q.F.; Li, J.; Yang, Y.
Abstract: In this work, we synthesized a FeCoNiCrCu high entropy alloy film (HEAF) via magnetron sputtering, which exhibited a metastable single FCC phase with random chemical distribution. Owing to the metastable nature, the as-deposited atomic structure affords nano-scale chemical fluctuation induced by moderate thermal annealing without causing phase transition. Compared to the single-phase FCC metals hitherto reported, our as-deposited and thermally annealed HEAFs exhibited the highest yield strength (3.4–4.2 GPa) under microcompression due to the combined action of nano-grains and growth twins. Furthermore, according to our experiments and atomistic simulations, plasticity-strength synergy was achieved as the nano-scale chemical fluctuation was able to promote deformation twinning in the HEAFs. The outcome of our research provides not only an atomistic understanding of the strength-plasticity synergy in the metastable FCC HEAFs with gigapascal yield strength, but also a facile method to design high performance metastable chemically complex metallic films. Highlights: Synthesis of metastable single phase FCC FeCoNiCrCu film. The strongest FCC crystals ever reported. The strength-plasticity synergy achieved via thermal annealing. The mechanism of plasticity revealed by modeling, experiments and simulations.